(untitled) (Discourse of Law and Administration, 2024)
This article explores very important difficulty in Polish-English legal communication. The problem is connected to Polish-English and English-Polish law dictionaries. In order to show this the translations from such dictionaries of basic terms connected to regulation of adverse possession in England were analysed.